Analysis of the Influence of Product Design on Consumer Purchasing Decisions - Bassam Al-Khouri; Omar Khan; Amir Raza (Journal of Loomingulisus ja Innovatsioon, 2025)
This research examines the influence of product design on consumer purchasing decisions. In the era of intense market competition, companies increasingly recognize that a well-designed product can be a significant factor in attracting consumers. Consumers are often influenced by the aesthetic appeal, usability, and functionality of a product before making a purchase decision. The objective of this study is to analyze the impact of various product design elements such as visual appeal, ergonomics, and brand identity on the purchasing decisions of consumers. This research uses a quantitative approach, employing surveys and questionnaires distributed to a sample of 200 consumers. Data analysis was conducted using descriptive statistics and regression analysis to determine the strength of the relationship between product design and purchasing decisions. The findings indicate that product design has a significant influence on consumer purchasing behavior. Among the design factors, visual appeal was found to have the strongest effect on consumers' decisions, followed by functionality and brand association. The study highlights that product design is not only a tool for differentiation but also a critical element in creating a positive consumer experience. In conclusion, companies should invest in innovative product designs to enhance consumer appeal and drive purchasing decisions.